EFFECTIVENESS AND SAFETY OF FAVIPIRAVIR INFUSION IN PATIENTS HOSPITALIZED WITH COVID-19 - L. A. Balykova; K. Ya. Zaslavskaya; V. F. Pavelkina; N. A. Pyataev; N. M. Selezneva; N. V. Kirichenko; A. Yu. Ivanova; G. V. Rodoman; K. B. Kolontarev; K. S. Skrupsky; E. N. Simakina; O. A. Mubarakshina; et al. (Фармация и фармакология (Пятигорск))
Research in the development of new therapeutic agents with a wide spectrum of the antiviral activity and a low ability to develop resistance remains the main dimension in combating the global threat to public health. The need for a parenteral form of favipiravir was dictated by the necessity to increase the efficacy of therapy in COVID-19 inpatients. This dosage form has expanded the possibilities of drug therapy in the inpatients, for whom a therapeutic effect acceleration and a high safety profile of the drugs used are especially important.The aim of the article is the evaluation of the efficacy and safety of a medicinal product containing favipiravir for the parenteral administration against the background of pathogenetic and symptomatic therapy, in comparison with standard therapy in hospitalized COVID-19 patients.Materials and methods. An open, randomized, multicenter comparative study was conducted in 6 research centers in the Russian Federation to evaluate the efficacy and safety of favipiravir, a lyophilisate for the preparation of a concentrate for the infusion solution administrated to the patients hospitalized with COVID-19. Screening procedures and randomization were completed in 217 patients, 209 of which had completed the study in accordance with the protocol.Results. Between the study groups, statistically significant differences have been found out, making it possible to consider the hypothesis of the drug Areplivir (favipiravir) superiority for the parenteral administration over the standard therapy, which included favipiravir (p. o.) and remdesivir. A comparative analysis has shown that a course of therapy with the parenteral favipiravir drug leads to a significant improvement in the condition of patients with COVID-19, significant benefits in terms of the speed and frequency of improvement in the clinical status of patients, as well as a reduction in the hospital stay length. It has been proven that therapy with a drug containing favipiravir for the parenteral administration does not adversely affect the parameters of clinical and biochemical blood tests, urinalysis, coagulograms, vital signs and ECG, which indicates the therapy safety. The study drug is characterized by a high safety profile and tolerability.Conclusion. The versatility and resistance to mutations of RNA-dependent RNA polymerase make it possible to consider it as the main target for combating the most common RNA viruses that cause ARVI, that determines the need  further studies of favipiravir to expand the range of its indications.